Aquagenic palmoplantar keratoderma associated with cystic fibrosis gene mutation - Falcão, Inês (2023)
Introduction: Aquagenic palmoplantar keratoderma (APK) is a rare dermatologic condition characterized by excessive palmar wrinkling that occurs within minutes of exposure to water. Cystic fibrosis (CF) or CF carrier-associated forms, drug-induced cases, and idiopathic forms have been described. The exact pathophysiology remains unknown. Clinical case: A 13-year-old female patient was observed for pruritus and palmar edema after brief contact with water with one month of evolution. Symptoms resolved spontaneously 20 minutes after drying the hands. Study of the cystic fibrosis transmembrane conductance regulator (CFTR) gene revealed an F508del mutation in one allele. Discussion/Conclusion: Similar to what was described in this patient, the F508del mutation has been the most commonly associated with APK in patients with CF. In the present case, APK was the sole manifestation of the patient's CF carrier status. This fact highlights the importance of considering and investigating this type of genetic alteration in these patients. Overall, CF should be considered in patients with APK, and patients with CF should be asked about symptoms of this condition.